The role of socio-emotional security on school engagement and academic achievement: systematic literature review - Dias, Pedro; Veríssimo, Lurdes; Carneiro, Alexandra; Duarte, Raquel (Frontiers in education (Lausanne), 2024)
IntroductionSocio-emotional security and particularly secure attachment relationships with parents and peers have been associated with positive developmental outcomes, including school-related variables. This systematic literature review aims to provide a comprehensive analysis of the literature, exploring the relationship between socio-emotional security (attachment, support, and secure relations with parents and peers) and academic achievement, school engagement, and early school dropout.MethodsThe inclusion criteria were studies with socio-emotional security as the independent variable and academic achievement and/or school engagement as the dependent variable, using a quantitative methodology, written in English. The exclusion criteria were articles presenting literature review or meta-analysis, interventions or instrument validation studies, studies with a qualitative approach, studies developed in an e-learning context, studies with university students, and/or focused on schooling in extreme conditions (e.g., COVID-19). PRISMA guidelines were followed, through a search that resulted in the identification of 38 empirical quantitative studies, published between 2018 and 2022, in English.Results and discussionThe results revealed that parent and peer relationships impact students’ academic achievement and school engagement, as expected, and highlighted the relevance of parental and peer relationships for school-related outcomes. Future research should consider the role of potential mediators and moderators in the relationship between socio-emotional security and school outcomes.